Farmer's Communication Network in Participation of Agricommerce Program in Batu City - Alia Fibrianingtyas; Mas Ayu Ambayoen (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2024)
Farmers need to use the Internet of Things (IoT) to modernize agriculture as a marketing medium, one of which is to address the marketing of agricultural products with perishable characteristics. Until now, the marketing system for agricultural products is still poorly understood by farmers, thus putting farmers in a weak bargaining position. One of the innovations developed in Batu City to address the modernization of marketing media is the Agricultural Product Promotion Program (Protan). This study aims to analyze the communication network of farmers formed in initiating the Agricultural Product Promotion Program (Protan). The research used a quantitative approach by interviewing farmers and collecting relevant literature. The research was conducted in 2023. In total, the respondents in this study were 43 people selected using snowball sampling. Communication network analysis was conducted using the UCINET communication network program version 6.0, applying the Adjacency Matrix (Full Matrix) data format. The variables used in this study include density, degree centrality, closeness centrality, betweenness centrality, and clique. The results showed that the communication network formed in the Agricultural Product Promotion Program (Protan) participation consisted of actors and nodes. The actor in this network is the head of the Farmer Assistance Program (TPP).